Use of graphs in the statistical modeling process - Hasmeek Wartan (College of Education for Pure Sciences, 2014)
Through studying numerical summaries and graph of data movement, to achieveproper and suitable type of data distribution, in simple, clear and minimizing errors, in the same time the graphs and summaries illustrate the possibility of unavailing of available distribution that we have, and the possibility of create data distribution in the case of disadvantages of identification to available data distribution